Poorer prognosis in patients with advanced gastric squamous cell carcinoma compared with adenocarcinoma of the stomach: Case report. Issue 50 (December 2017) - Meng, Ying; Zhang, Jiazhao; Wang, Huijun; Zhang, Yiping; Sun, Ruirui; Zhang, Zhen; Gao, Fang; Huang, Chengsuo; Zhang, Shu
Abstract: Rationale: Primary squamous cell carcinoma (SCC) of the stomach is a rare disease. The pathogenesis and prognosis of advanced SCC remains to be elucidated. The aim of the current study was to investigate the prognosis of recurrent or metastatic SCC of the stomach. Patient concerns: A retrospective study examined the clinical characteristics and survival outcomes of 14 patients diagnosed with recurrent or metastatic SCC of the stomach, including 7 patients followed up in the hospital and 7 patients selected from the PubMed and Chinese National Knowledge Infrastructure (CNKI) database with meta-analysis between January 2003 and January 2016. Diagnoses: All patients meet the following diagnoses criteria: histological diagnosis of gastric squamous cell carcinoma; the tumor must not be located in the cardia area or extend into the esophagus; presence of local relapse or distant metastases of gastric SCC in computed tomography (CT) images; and no evidence of secondary SCC in the body. Clinical pathological data and follow-up data were obtained from the medical record or case report of each patient. Interventions: Palliative chemotherapy was administered in 14 patients diagnosed with recurrent or metastatic gastric SCC. Outcomes: The median age of 14 patients (10 males and 4 females) was 61 years old (range, 28–76). In total, 57% (8/14 cases) of tumors were located on the lesser curvature side of the stomach and 64% (9/14 cases) of metastatic sites were identified in the liver. All patients received systemic chemotherapy, and their median survival was 7.0 months (range, 2.0–22.3 months). Lessons: The median survival of patients with advanced gastric SCC was shorter than the median survival (11 months) of advanced gastric adenocarcinoma, suggesting that advanced gastric SCC may have a poorer prognosis compared with adenocarcinoma of the stomach in recurrent or metastatic stage.